A novel method for laser radar cross section calculation of complex laser targets with partial and Gaussian beam irradiation. (23rd October 2018) - Wang, Qianqian; Zhao, Jing; Shan, Bin; Li, Xiaoyang
Abstract: A directional-diffuse light (DDL) algorithm is proposed to calculate the laser radar cross section of complex targets with partial irradiation by changing the size of the viewing volume based on graphical electromagnetic computing and OpenGL. To assess the performance of the DDL algorithm, we theoretically and experimentally compare the DDL algorithm with the spotlight (SL) algorithm: another algorithm used in partial irradiation cases. We find that there is a higher degree of consistency between the theoretical or experimental and simulated data calculated by the DDL algorithm compared with the SL algorithm. Moreover, we propose a directional-diffuse Gaussian light (DDGL) algorithm by including an attenuation factor for characterizing the transverse intensity profile of the Gaussian laser beam based on the DDL algorithm. We theoretically and experimentally analyze the effects of the DDGL algorithm and the DDL algorithm and show that the DDGL algorithm efficiently improves the accuracy of numerical simulation relative to the DDL algorithm. Finally, we compare the experimental data with the simulated data calculated by the DDGL algorithm at different in-plane bistatic angles. The experimental results demonstrate that the DDGL algorithm can accurately illustrate laser scattering properties of targets with partial and Gaussian beam irradiation.